2016
DOI: 10.1101/076364
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cellobiose consumption uncouples extracellular glucose sensing and glucose metabolism inSaccharomyces cerevisiae

Abstract: Glycolysis is central to energy metabolism in most organisms and is highly regulated to enable optimal growth. In the yeast Saccharomyces cerevisiae, feedback mechanisms that control flux through glycolysis span transcriptional control to metabolite levels in the cell. Using a cellobiose consumption pathway, we decoupled glucose sensing from carbon utilization, revealing new modular layers of control that induce ATP consumption to drive rapid carbon fermentation. Alterations of the beta subunit of phosphofruct… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…3). Furthermore, a recent study revealed that the plasma membrane ATPase (PMA1) of cellobiose-fermenting S. cerevisiae is in a carbon starvation-like state [60]. Although we unable to exactly pinpoint the cause of the reduced TaBgl1 glycosylation in cellobiose-containing medium, we propose that carbon starvation-like state may be at least in part responsible for that.…”
Section: Discussionmentioning
confidence: 57%
“…3). Furthermore, a recent study revealed that the plasma membrane ATPase (PMA1) of cellobiose-fermenting S. cerevisiae is in a carbon starvation-like state [60]. Although we unable to exactly pinpoint the cause of the reduced TaBgl1 glycosylation in cellobiose-containing medium, we propose that carbon starvation-like state may be at least in part responsible for that.…”
Section: Discussionmentioning
confidence: 57%
“…Transcriptional and metabolite profiling have revealed that yeast cells fermenting cellobiose are subjected to severe physiological changes, compared to cells fermenting glucose, as reflected in the activation of mitochondrial function and a decrease in amino acid biosynthesis, and in a carbon starvation-like state of the plasma membrane ATPase (Pma1) (Lin et al 2014;Chomvong et al 2017). Furthermore, when cultivated in cellobiose medium, yeast cells accumulate high levels of trehalose and of intermediate metabolites in the γ-aminobutyrate (GABA) shunt pathway, improving the strain's tolerance to oxidative stress (Kim et al 2014b;Yun et al 2018).…”
Section: The Icell Componentmentioning
confidence: 99%